2015
DOI: 10.1155/2015/160979
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Directed Resuscitation Aiming Cardiac Index Masks Residual Hypovolemia: An Animal Experiment

Abstract: The aim of this study was to compare stroke volume (SVI) to cardiac index (CI) guided resuscitation in a bleeding-resuscitation experiment. Twenty six pigs were randomized and bled in both groups till baseline SVI (T bsl) dropped by 50% (T 0), followed by resuscitation with crystalloid solution until initial SVI or CI was reached (T 4). Similar amount of blood was shed but animals received significantly less fluid in the CI-group as in the SVI-group: median = 900 (interquartile range: 850–1780) versus 1965 (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…: MAP~60–65 mmHg) by most guidelines (4). Our current findings are in accord with that of published earlier in similar animal experiments, when bleeding caused almost identical changes in blood pressure, t bsl :112±23 to t 0 : 74±18 mmHg, p <0.05 [ 16 , 17 ]. Therefore, MAP may not only be an inappropriate resuscitation target but may also be an inadequate parameter to commence fluid resuscitation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…: MAP~60–65 mmHg) by most guidelines (4). Our current findings are in accord with that of published earlier in similar animal experiments, when bleeding caused almost identical changes in blood pressure, t bsl :112±23 to t 0 : 74±18 mmHg, p <0.05 [ 16 , 17 ]. Therefore, MAP may not only be an inappropriate resuscitation target but may also be an inadequate parameter to commence fluid resuscitation.…”
Section: Discussionsupporting
confidence: 94%
“…Cardiac output is a major determinant of DO 2 , and several studies encourage optimization of cardiac output during fluid therapy [ 26 , 27 ]. However, our previous series of animal experiments revealed that CO also has pitfalls as a therapeutic end-point [ 16 , 17 ]. Comparing CO-, vs. SV-guided resuscitation, the latter provided sufficient restoration of bleeding caused hemodynamic disturbances, while CO normalized because of persistent tachycardia, resulting in residual hypovolemia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We applied a model which has been tested and reported in our previous experiments [ 22 , 23 ]. The study protocol is summarized in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, kidney-targeted approaches could improve patients’ outcomes. The current treatment approach is based on restoration of the macrohemodynamics such as blood pressure and heart rate during hemorrhagic shock [19, 20]. Fluid treatments are used as the first step for normalization deteriorated macrohemodynamics.…”
Section: Discussionmentioning
confidence: 99%